Culture and conquest in Mongol Eurasia - Allsen, Thomas T. (Cambridge studies in Islamic civilization., 2001)
"In the thirteenth century the Mongols created a vast transcontinental empire that functioned as a cultural "clearing house" for the Old World. Under Mongol auspices various commodities, ideologies, and technologies were disseminated and displayed across Eurasia. The focus of this path-breaking study is the extensive exchanges between Iran and China. The Mongol rulers of these two ancient civilizations "shared" the cultural resources of their realms with one another. The result was lively traffic in specialist personnel and scholarly literature between East and West. These exchanges ranged from cartography to printing, and from agriculture to astronomy. Unexpectedly, the principal conduit of this transmission was an obscure Mongol tribesman, Bolad Aqa, who first served Chinggisid rulers of China and was then posted to Iran where he entered into a close and productive collaboration with the famed Persian statesman and historian. Rashid al-Din. The conclusion of the work examines why the Mongols made such heavy use of sedentary scholars and specialists in the elaboration of their court culture and why they initiated so many exchanges across Eurasia. The book is informative and erudite. It crosses new scholarly boundaries in its analysis of communication and culture in the Mongol Empire and promises to become a classic in the field."--Jacket